A novel analytical approach to describe the simultaneous diffusional growth of multilayer stoichiometric compounds in binary reactive diffusion couples. (15th January 2021) - Ma, Sa; Xing, Fangzhou; Deng, Chunming; Zhang, Lijun
Abstract: In this paper, we developed a novel analytical approach for description of the diffusion-controlled simultaneous growth of multilayer stoichiometric compounds in binary reactive diffusion couples. The approach was directly extended to describe the compounds with narrow/certain homogeneity ranges. The models were then applied to three different real cases in technically important Co–Si and Cu–In binary systems. The predicted thickness curves/composition profiles revealed a satisfactory agreement with all the experimental data. The successful applications indicate that the approach can serve as an efficient way for describing the multi-layer growth in the joining, coating, and solar cell industries. Graphical abstract: Image, graphical abstract